Proceedings of meetings on acoustics - Acoustical Society of America; Acoustical Society of America. Meeting (Acoustical Society of America, 2008)
Includes the proceedings of the meetings of the Acoustical Society of America (beginning with the 153rd meeting held in 2007) and the International Conference on Nonlinear Elasticity in Materials (beginning with the 13th conference held in 2008).
Keywords: Sound : Congresses; Acoustical engineering : Congresses; Acoustical engineering; Sound